2019
DOI: 10.1177/1747021819836890
|View full text |Cite
|
Sign up to set email alerts
|

Breaking voice identity perception: Expressive voices are more confusable for listeners

Abstract: The human voice is a highly flexible instrument for self-expression, yet voice identity perception is largely studied using controlled speech recordings. Using two voice-sorting tasks with naturally varying stimuli, we compared the performance of listeners who were familiar and unfamiliar with the TV show Breaking Bad. Listeners organised audio clips of speech with (1) low-expressiveness and (2) high-expressiveness into perceived identities. We predicted that increased expressiveness (e.g., shouting, strained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 27 publications
11
66
2
Order By: Relevance
“…failing to perceive different exemplars of the same voice as belonging to the same identity). This study thus replicated previous findings from face sorting tasks (Jenkins et al, 2011, Zhou & Mondloch, 2016. Sorting tasks provide a powerful method to explore identity processing for naturally-varying voices, while also allowing for comparisons of familiar and unfamiliar participants' behaviour within the same task.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…failing to perceive different exemplars of the same voice as belonging to the same identity). This study thus replicated previous findings from face sorting tasks (Jenkins et al, 2011, Zhou & Mondloch, 2016. Sorting tasks provide a powerful method to explore identity processing for naturally-varying voices, while also allowing for comparisons of familiar and unfamiliar participants' behaviour within the same task.…”
Section: Introductionsupporting
confidence: 83%
“…Sorting tasks provide a powerful method to explore identity processing for naturally-varying voices, while also allowing for comparisons of familiar and unfamiliar participants' behaviour within the same task. For face perception, sorting tasks have recently been used to probe more nuanced aspects of identity processing: Zhou and Mondloch (2016) report an other-race effect in a face sorting task for unfamiliar but not familiar participants. Redfern and Benton (2017) used a sorting task to investigate the role of facial expressiveness on identity perception using naturally-varying pictures of individuals unknown to the participants: when contrasting high-expressiveness with low-expressiveness faces in two sorting tasks, viewers made significantly more errors for "telling people apart" when sorting highly expressive faces, by mixing pictures of different people into a single perceived identity.…”
Section: Introductionmentioning
confidence: 99%
“…There is also preliminary evidence that within each sex, F0 in modal speech correlates with F0 in sung speech [20], and that cues to individual identity are retained in valenced human speech [21], laughter [22], cries [23], and in the screams of both humans ( [24], cf. [25]) and non-human primates [26] (with the caveat that speaker recognition is substantially reduced from these vocalizations compared to modal speech among human listeners [21,22,25]). Finally, longitudinal studies have recently revealed that individual differences in F0 remain relatively stable across the lifespan, from infancy to childhood and throughout adulthood [27,28].…”
Section: Introductionmentioning
confidence: 95%
“…Listeners often fail to reliably discriminate between talkers when exposed to voices disguised using falsetto, hyponasality, creaky voice, or whispering (Hirson and Duckworth, 1993;LaRiviere, 1975;Reich and Duke, 1979;Reich et al, 2005;Wagner and Köster, 1999); and changes in a speaker's emotional state substantially impair listeners' abilities to recognize Saslove and Yarmey 1980;cf. Read and Craik 1995) or discriminate among talkers (Lavan et al, 2019). Within-talker variability can also interfere with a listener's ability to judge that samples come from the same (rather than different) talkers.…”
Section: Introductionmentioning
confidence: 99%